Critical issues in electronic media - Penny, Simon (SUNY series in film history and theory., 1995)
Critical Issues in Electronic Media is an interdisciplinary sourcebook that offers new critical perspectives directly related to, or arising from, the practice of electronic media art. It sketches the changing topology of culture as it enters electronic space and specifically addresses questions of art practice in that space. Some of the contributions focus on the dynamics of specific emerging media such as interactive media, while others look at the cultural conditions formed by, and forming around, new technological complexes. Still others examine contemporary technocultural manifestations against a background of social and technological history. The contributors are professionally and geographically diverse, representing professional fields such as computer graphics, video, sound, drama, and visual arts as well as media, cultural and literary theory, and the social sciences. Together, these essays provide a rich survey of contemporary technological critique and offer a perspective on creative practice in technological media.